TYPES OF DENTAL WEAR AND THEIR ETHIOLOGY - Earar Kamel; Madalina Nicoleta Matei (Romanian Society of Oral Rehabilitation, 2017)
Dental wear is a universal experience; it is accepted today that the phenomena of dental wear know a significant increase especially in young people. Although the causes are not well defined, it is supposed to act as a category of "predisposing factors" specific to age and civilization as well as a category of causal factors.Aim of the study :Our researches included two aspects: one clinical and one laboratory. The data were recorded in dental records and analyzed in order to identify the various etiological correlations. Material and methods:The odontal examination was performed only after the oral cavity was cleaned, the reduction of the gingival inflammation and the professional brushing. I recorded the cavities and cavities, the various abrasive grades and the dental areas interested in cervical erosions, using direct or projected light and the magnifying glass or microcameras .Results and discussions: Loss of hard dental substance of a non-causative etiology is a normal physiological process that takes place throughout life. Identifying the causes involved in this process is particularly important in order to predict the long-term behavior of both teeth and restorative treatments. It is difficult to determine the limit to which tissue loss is considered pathological because the notion of normal is still a source of controversy. With regard to the data as a whole we can say that in our study of the type of dental erosion, moderate erosion had a higher frequency: slight erosions - 26.24%, moderate erosions - 50%, severe erosions - 13.76% Conclusions:The dental wear term denotes the progressive loss of dental hard tissue due to three processes: abrasion (wear caused by tooth interaction with other materials), atrium (wear due to tooth contact on the tooth) and erosion (dissolution of dental hard tissue due to the acidic substances).